Structured interaction between teacher and student in the flipped classroom enhances learning and interbrain synchrony - Qi Li; Die Wang; Weilong Xiao; Yingying Tang; Qi Sun; Binghai Sun; Zhishan Hu (npj Science of Learning)
Abstract Studies have found that flipped classroom teaching (FT) improves learning compared to lecture-based teaching (LT). However, whether the structured teacher–student interaction—the key feature of FT—plays an essential role in enhancing learning remains unclear, as do its neural underpinnings. Here, we compared three teaching conditions: FT with a video lecture and structured interaction, LT with a face-to-face lecture and spontaneous interaction, and control teaching (CT) with a video lecture and spontaneous interaction. The fNIRS-based hyperscanning technique was used to assess the interbrain synchrony (IBS) from teacher-student dyads. Results showed that the learning was significantly improved in FT than in LT and CT, and FT significantly increased teacher–student IBS in left DLPFC. Moreover, the IBS and learning improvements were positively correlated. Therefore, these findings indicate that the structured teacher–student interaction is crucial for enhancing learning in FT, and IBS serves as its neural foundation.